Performance Enhancement of Microbial Fuel Cells from Fishery Wastewater Using Boost Converter Device - Ibrahim, Bustami; Uju; Subrata, I Dewa Made; Ramadhan, Rahmat Agung (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2024)
Electricity is a fundamental need in daily life. Fossil energy is commonly used to generate electricity; however, as a non-renewable resource, it will eventually be depleted without innovations involving renewable energy. Fishery wastewater can generate electricity using the Microbial Fuel Cell (MFC) system. However, the electricity produced is relatively low. This study aims to increase the electrical voltage generated from pindang fish wastewater in an MFC system by integrating a boost converter circuit. The research was conducted using five MFC systems connected in series and linked to a boost converter. The electrical output of the MFC system with the boost converter circuit showed a voltage of 12.13±0.87 V, a current of 0.86±0.20 mA, and a power output of 10.50±3.11 mW. In contrast, the system without the boost converter produced a voltage of 2.24±0.26 V, a current of 0.17±0.03 mA, and a power output of 0.38±0.11 mW. The increase in electricity output demonstrates the functionality of the boost converter circuit. Additionally, the MFC system effectively reduced BOD, COD, and TAN values in the fishery wastewater.